Financing the energy transition: The role, opportunities and challenges of green bonds - Andrea Giulio Maino (The Oxford Institute for Energy Studies, 2022)
This paper discusses the current developments and adoption of financial instruments designed to support the efforts of governments and corporations in decarbonizing their activities. Particular focus is given to the role of Green Bonds, a debt-like financial instrument whose proceeds are used to finance 'Green' projects/assets. Green bonds have experienced strong growth at the global level and represent, as of 2021, a USD1.5 trillion market, with issuers including governments, supranational institutions, and corporates. Among corporate issuers within the energy sector, utility firms stand out as early adopters, motivated by their investments in renewable infrastructure as part of their strategy to reduce greenhouse gas (GHG) emissions. From the issuers' perspective, several incentives motivate the issuance of green bonds including i) diversifying their investor base, ii) accessing a larger and more stable investor base, and iii) signalling strong commitment to credible decarbonization strategies. These incentives are considered to compensate for the additional costs incurred by third-party verification and enhanced post-issuance reporting. This paper reviews evidences on the 'greenium' - namely the premium paid by investors on green bonds and also discusses the important role played by institutional investors and financial institutions in the green bond market. Central banks are also expected to play a major role in shaping the pricing and adoption of green finance - and green bonds in particular - by providing guidance and adapting their supervisory and monetary interventions. The paper concludes by reviewing more recent 'green' financing instruments, such as Sustainability Bonds and, in particular, Sustainability-Linked Bonds, as they are of particular relevance for the energy industry and hard-toabate sectors.
Keywords: 330; Financing Energy Transition; green bonds; green financing; Sustainability-Linked bonds